Pengembangan Pembelajaran Bahasa Arab di Rumah Pada Masa Covid 19 - Musnif Istiqomah; R.Umi Baroroh (STAIFAS-Press, 2021)
In the situation of the covid-19 pandemic, the education system began to look for an innovation for the process of teaching and learning activities. With the Circular No. 4 of 2020 from the Minister of Education and Culture which recommends that all activities in educational institutions must keep a distance and all material delivery is delivered at their respective homes, inevitably parents take the role of learning companions who are actively involved and responsible. responsible for all learning at home, including learning Arabic. Arabic learning is aimed at encouraging, guiding, developing, and fostering abilities and fostering a positive attitude towards Arabic, both receptively and productively. Acting as a home study companion, parents need guidance during the Arabic learning process. This paper is the result of a qualitative research that describes what the author did for 2 semesters in accompanying his son who was in grade 1 of Madrasah Ibtidayyah while learning Arabic at home. So that this paper can be guided by parents in accompanying their children while learning Arabic at home. The conclusion of this paper is that the development of Arabic learning at home is carried out to support Arabic learning in madrasas/schools. Parents have an important role in encouraging and growing children's positive attitudes towards Arabic. Parents as learning companions also have a strategic role in achieving Arabic learning goals in schools/madrasas. Keywords: Arabic Learning Development, Arabic Learning Companion at Home